Konkurencja między jednostkami terytorialnymi a efektywność gospodarki - Zalewski, Alojzy (Competition Among Territorial Units and Economic Efficiency, 2006)
The paper attempts to assess the impact of competition among territorial units on the economic efficiency. It starts with an analysis of the mechanisms of territorial competition which then serves as a basis for the assessment of influence of various instruments of competition on micro- and macro-economic efficiency. The analysis included several kinds of competition, namely: financial competition, infrastructural competition, environmental competition (creation of environment conducive to innovation and entrepreneurship) and information competition. The findings have shown that financial competition leads to zero-sum game and benefits investors and winning territorial units only. On the other hand, infra-structural and environmental competition improve both microeconomic and macroeconomic efficiency. The information competition facilitates the choice of location for investment, but does not settle it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 253-263